Chances of Employment in a Population of Women and Men after Surgery of Congenital Heart Disease: Gender-Specific Comparisons between Patients and the General Population - Siegfried Geyer; Kambiz Norozi; Reiner Buchhorn; Armin Wessel (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
It was examined whether women and men (17-45 years) with operated congenital heart disease (CHD) differ with respect to chances of employment. Patients were compared with the general population. Patients (N=314) were classified by type of surgery (curative, reparative, palliative) as indicator of initial severity of disease. The second classification was performed according to a system proposed by the New York Heart Association in order to take subjectively reported impairments into account. Controls (N=1165) consisted of a 10% random sample drawn from the German Socio-Economic Panel. Chances of full- time employment decreased as disease severity increased. Chances of part- time and minor employment were higher in patients than among controls. These general effects were due to male patients, while the employment patterns of women did not differ from the control group. Independently of patient status women were more likely to have lower rates of full- time employment, and the rates of part- time and minor employment were higher. Long- term adaptation to impairments due to congenital heart disease differs between women and men with respect to employment status. While female patients do not differ from the general population, males may lower their engagement in paid work.
Keywords: 330